Patients’ and therapists’ experiences of general change mechanisms during bug-in-the-eye and delayed video-based supervised cognitive-behavioral therapy: a randomized controlled trial - Probst, Thomas; Bohus, Martin (Journal of clinical psychology, 2018)
Objective: This secondary analysis of a randomized controlled trial investigated whether bug-in-the-eye (BITE) supervision (live computer-based supervision during a psychotherapy session) affects the manner in which patients and therapists experience general change mechanisms (GCMs) during cognitive-behavioral therapy (CBT). Method: A total of 23 therapists were randomized either to the BITE condition or the control condition (delayed video-based [DVB] supervision). After each session, both patients (BITE: n = 19; DVB: n = 23) and therapists (BITE: n = 11; DVB: n = 12) completed the Helping Alliance Questionnaire (HAQ) and the Bernese Post Session Report (BPSR). The HAQ total score and the 3 secondary factors of the BPSR (interpersonal experiences, intrapersonal experiences, problem actuation) functioned as GCMs. Multilevel models were performed. Results: For patients, GCMs did not develop differently between BITE and DVB during CBT. Therapists rated the alliance as well as interpersonal and intrapersonal experiences not significantly different between BITE and DVB during CBT, but they perceived problem actuation to increase significantly more in BITE than in DVB (p < .05). Conclusion: BITE supervision might be helpful in encouraging CBT therapists to apply interventions, which focus on the activation of relevant problems and related emotions.